2020
DOI: 10.1051/matecconf/202032902005
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a multicomponent FeCoCrAlTiCuMo alloy coating applied by a combined process based on atmospheric plasma metallization

Abstract: A brief analysis of the most common methods for producing multicomponent alloys, including high-entropy alloys (HES), is presented in terms of their use as an alternative to coatings made of traditional structural metal materials. Preliminary studies of the microstructure and phase composition of the coating obtained by plasma deposition of FeCoCrAlTiCuMo powder in the equiatomic ratio of components are presented . The results of the research showed the possibility of obtaining a multicomponent single-phase so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
0
0
1
Order By: Relevance
“…This is indirectly confirmed by the wear test results, which showed that multiple coating reflow led to a noticeable increase in its wear resistance under dry friction conditions, accompanied by significant frictional heating of the surface. The obtained results confirm the assumption about the possibility of obtaining single phase multicomponent alloys with a high entropy of mixing by plasma spraying in combination with multiple reflow and indicate the advisability of deeper studies [20].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is indirectly confirmed by the wear test results, which showed that multiple coating reflow led to a noticeable increase in its wear resistance under dry friction conditions, accompanied by significant frictional heating of the surface. The obtained results confirm the assumption about the possibility of obtaining single phase multicomponent alloys with a high entropy of mixing by plasma spraying in combination with multiple reflow and indicate the advisability of deeper studies [20].…”
Section: Discussionsupporting
confidence: 82%
“…The studies of multicomponent alloy FeCoCrAlTiCuNiMo in equiatomic component ratio obtained by a combined process based on the plasma atmospheric spraying with multiple reflow showed the possibility to obtain the single-phase solid solution [19]. The alloy disadvantages caused by its heterogeneity in structure can be minimized by multiple reflow of the coating surface, which contributes to the completion of diffusion processes, the coating composition homogenization, the new structures forming, increasing of fatigue resistance and a growth in entropy.…”
Section: Discussionmentioning
confidence: 99%
“…Результаты проведенных исследований многокомпонентного сплава FeCoCrAlTiCu-NiMo в эквиатомном соотношении компонентов, полученного атмосферным плазменным напылением, показали возможность получения однофазного твердого раствора, используя технологию плазменного напыления [15][16][17][18][19][20]. Недостатки сплава, вызванные его неоднородностью по структуре возможно минимизировать путем кратного оплавления поверхности покрытия, которое способствует завершению диффузионных процессов, гомогенизации состава покрытия, формированию новых структур, повышению усталостной прочности и росту энтропии.…”
Section: обсуждение и заключениеunclassified